Redesign wheelchairs for stroke sufferers using the Quality Function Deployment method - Apriani, Ratna Agil; Purnomo, Hari (SINERGI, 2024)
The prevalence of stroke in Indonesia continues to increase, so there is a need for mobility assistance. In today's era, high mobility is necessary to live with freedom, but stroke sufferers still struggle to achieve comfort when using this mobility, namely wheelchairs. The author conducted research to redesign a wheelchair that is tailored to the needs of stroke sufferers. This research was conducted using the Quality Function Deployment method to obtain information on the needs of stroke sufferers and the Wilcoxon Difference Test method to determine the level of difference between old wheelchair designs and improvements. The results showed that the wheelchairs needed by stroke sufferers were multifunctional, ergonomic, flexible, safe, and materially sound. In the results of the Wilcoxon Difference Test, which was carried out based on the hypothesis, it is known that only the flexible attribute has no difference compared to the previous wheelchair design product. In contrast, the other four attributes have different values for the old wheelchair design and the improved design. Thus, redesigning wheelchairs is accomplished by obtaining design specifications that meet the needs of stroke sufferers.